Economic Integration, Sectoral Diversification, and Exchange Rate Policy in a Developing Economy - Srour, Gabriel (IMF Working Papers; Working Paper ;, 2004)
The paper develops a simple three-sector model of a developing country with nominal wage rigidity, in which one sector is thought of as the primary sector and the other two are sectors in which the country can diversify. The paper then analyzes the relationship between the market structure of the nonprimary sectors and equilibrium adjustments to shocks in the primary sector. In particular, the paper examines under what conditions the country should promote one nonprimary sector over another. Among other things, it argues that developing countries should promote those sectors that are more integrated with the outside world.